Implementation of Criminal Sanctions in Falsification of Tax Returns that Harm the State - Mutiara Fadia Silalahi; Ismail Koto (Melayunesia Law, 2024)
Crime can occur in various aspects including tax administration which leads to tax crimes. The application of criminal sanctions against falsification of tax notification letters that harm the state must be optimised. This research raises issues related to how the application of criminal law arrangements regarding falsification of tax notification letters that harm the state? how the application of criminal law sanctions against falsification of tax notification letters that harm the state? how criminal law efforts in applying sanctions against falsification of tax notification letters that harm the state? The purpose of this research is to answer the problems that are the issue of this research discussion. The importance of this topic of discussion is to provide education to the public regarding the legal consequences of the crime of forgery of letters that harm the state. This research uses a normative juridical method that priority the study of laws and regulations (library research). This research has findings, namely this research recommends strengthening the legal substance sector through the issuance of tax counterfeiting laws with heavier sanctions accompanied by restitution to the state.